Enhancing English as a Foreign Language Reading Proficiency: Key Skills for Comprehension and Engagement - Hery Yanto The (Universitas Muria Kudus, 2024)
A high level of competence in reading English as a second language is crucial for achieving academic excellence and personal growth. This concept paper outlines methods for improving students' English as a Foreign Language reading ability. The approach involves extracting reading methods from main journal articles, practicing and analyzing reading extracts, and combining them to practice essential reading skills. The aim of this study is to establish a foundation for reading by emphasizing key elements such as reading methods, understanding various types of texts, critical thinking, and inference abilities, considering cultural context in reading, and assessing and tracking reading skill growth. The interdependent elements mutually reinforce one another, as fluency enhances understanding and understanding facilitates the increase of vocabulary. Evidence suggests that employing good reading techniques, such as skimming, scanning, and detailed reading, enables pupils to traverse texts proficiently and comprehend essential concepts and particulars. Gaining knowledge of different literary genres and text structures improves overall reading proficiency, while cultivating analytical thinking abilities enables students to deduce, assess arguments, and form conclusions supported by textual evidence. Understanding the cultural background of books helps to interpret their meanings and subtle details, enhancing the reading experience. Consistent evaluation and surveillance of reading progress ensures that students recognize areas in need of improvement and evaluate their growth over time. By understanding and using the skills presented in this paper, English as a Foreign Language learners can improve their reading proficiency, positioning themselves for enduring achievement in academic, professional, and social environments.